Sociodemographic factors associated with alcohol consumption among men in Gabon: insights from the Gabon demographic and health survey of 2019–2021 - Mankelkl, Gosa; Kinfe, Beletu (Frontiers in Public Health, 2025)
BackgroundAlcohol is a psychoactive drug that can lead to dependence and has been used extensively for centuries in many different cultures. The primary driver of alcohol consumption is likely its capacity to elevate mood and alleviate stress. More than 200 medical conditions, including liver diseases, traffic accidents, violence, cancer, heart disease, suicide, tuberculosis, and HIV/AIDS, have been causally associated with alcohol consumption. According to estimates from the World Health Organization, 3 million people die from alcohol-related causes globally each year. In other words, 5.3% of all fatalities in the world each year are related to alcohol. Although a majority of research has been conducted in Gabon on this particular subject in a variety of contexts, most of the studies were not representative. Consequently, this study’s primary goal was to evaluate sociodemographic factors associated with alcohol consumption among men in Gabon using data from the most recent national Gabon Demographic and Health Survey.MethodsFor this secondary data analysis, the most recent datasets from the Gabon demographic and health survey were used. A total of 6,894 men participated in this study. The bivariate analysis was used to select the factors for the multivariable analysis. Factors with a p < 0.05 significance level were considered significant predictors of alcohol consumption among men in the multivariate analysis. Finally, the 95% confidence intervals for the percentage and odds ratio were reported.ResultsThis study includes a total weighted sample of 6,894 men from the Gabon Demographic and Health Survey. The national prevalence of alcohol consumption among men in Gabon was 63.50%, with a 95% confidence interval (CI) of 62.36–64.63. Factors negatively associated with alcohol consumption among men included being above the age of 50 years [AOR: 0.272, 95% CI (0.212, 0.347)], residing in urban areas [AOR: 0.792, 95% CI (0.691, 0.908)], having higher education [AOR: 0.415, 95% CI (0.292, 0.590)], living with a partner [AOR: 0.682, 95% CI (0.570, 0.815)], and listening to the radio [AOR: 0.716, 95% CI (0.632, 0.811)]. In contrast, being a follower of the revival church [AOR: 14.287, 95% CI (11.117, 18.360)] was positively associated with alcohol consumption.ConclusionAlcohol consumption among men has been associated with sociodemographic characteristics. Therefore, to reduce alcohol consumption among men, the government of Gabon and other relevant stakeholders should focus on younger men, particularly those living in urban areas and those who have not received formal education. Additionally, media campaigns highlighting the adverse effects of alcohol consumption should be promoted through radio.